Over-Expression of 60s Ribosomal L23a Is Associated with Cellular Proliferation in SAG Resistant Clinical Isolates of Leishmania donovani - Das, Sanchita (Public Library of Science, 2013)

(untitled)
BACKGROUND: Sodium antimony gluconate (SAG) unresponsiveness of Leishmania donovani (Ld) had effectively compromised the chemotherapeutic potential of SAG. 60s ribosomal L23a (60sRL23a), identified as one of the over-expressed protein in different resistant strains of L.donovani as observed with differential proteomics studies indicates towards its possible involvement in SAG resistance in L.donovani. In the present study 60sRL23a has been characterized for its probable association with SAG resistance mechanism. METHODOLOGY AND PRINCIPAL FINDINGS: The expression profile of 60s ribosomal L23a (60sRL23a) was checked in different SAG resistant as well as sensitive strains of L.donovani clinical isolates by real-time PCR and western blotting and was found to be up-regulated in resistant strains. Ld60sRL23a was cloned, expressed in E.coli system and purified for raising antibody in swiss mice and was observed to have cytosolic localization in L.donovani. 60sRL23a was further over-expressed in sensitive strain of L.donovani to check its sensitivity profile against SAG (Sb V and III) and was found to be altered towards the resistant mode. CONCLUSION/SIGNIFICANCE: This study reports for the first time that the over expression of 60sRL23a in SAG sensitive parasite decreases the sensitivity of the parasite towards SAG, miltefosine and paramomycin. Growth curve of the tranfectants further indicated the proliferative potential of 60sRL23a assisting the parasite survival and reaffirming the extra ribosomal role of 60sRL23a. The study thus indicates towards the role of the protein in lowering and redistributing the drug pressure by increased proliferation of parasites and warrants further longitudinal study to understand the underlying mechanism.